Simulação Numérica de Grandes Escalas da Convecção Natural em Cavidades Anulares com Fontes e Sumidouros de Calor - Ferreira, Dálglis Shilton Silva (2017)
In the current industry, is notorious the presence of problems involving fluid dynamics with heat transfer. In this context, problems where the heat transfer occurs over heated cylinders deserves a special attention. The present work study aimed to develop a three-dimensional numerical analysis of the heat transfer by natural convection in concentric cylinders in the presence of discrete heat source-sink pairs, with emphasis on the study of stable-unstable regime flow (air working fluid). The numerical code was developed in cylindrical coordinates, discretized using the finite volume technique and temporal/ spatial schemes of second order, where the pressure-velocity coupling is done through the fractional step method. Through velocity, temperature and vorticity fields, it was found that the heat transfer is affected by the first instabilities in the unstable regime. It was also possible to verify the destabilization of the flow with a thin mesh. Moreover, the data obtained showed an excellent agreement with the experimental data found in the literature, especially in the stable regime.